Celebricities : media culture and the phenomenology of gadget commodity life - Adler, Anthony Curtis (Idiom (Fordham University Press), 2016)
"Taking its departure from a phenomenological encounter with television--indeed a rethinking of the phenomenological method in terms of the way in which the experience of television disarticulates life, opposing my life to the life that is not mine to live and yet mine not to live--this book attempts to illuminate the ontology of late capitalism, focusing on celebrity culture and the rise of the pluripotent gadget. While Heidegger's analysis of Dasein in Being and Time will serve as the starting point, the theorization of the gadget in particular proceeds by means of bringing Heidegger's ontology into dialogue with the Marxist theory of the commodity and Althusser's treatment of ideology. Gadget-commodity-life will come to be understood in terms of a reproduction of the "alethic," rather than merely ideological, conditions of production. For production to remain possible it will become increasingly necessary to have the commodity itself "stage" the play of concealment-unconcealment as the ontological basis of production. Whereas the first part of this book develops a theoretical frame work through a sustained argument, the second part will attempt to "screen" television, celebrity, and gadget-commodity-life itself through a series of fragmentary theoretical encounters. These will attempt, moreover, to show how the pop-culture objects of late capitalism exist only through the possibility of a theoretical encounter with them--or, in other words, exist as phenomenological."